Rural Transformation and Newfoundland and Labrador Diaspora
XX, 436 p.
Keywords: This book is endorsed by Dr. Clar Doyle in his preface to this book. Dr. Doyle is very well known locally. This book is about the contemporary life of grandparents in Newfoundland and Labrador – a geographically isolated and culturally unique rural region of Canada. The book can be used for courses in the areas of critical social work, family studies, gerontology, nursing, rural development, critical pedagogy, and diaspora studies. Clar Doyle, Professor of Education, Memorial University of Newfoundland, and member of the Founding Scholars Advisory Board, The Paulo and Nita Freire International Project for Critical Pedagogy. “This book offers a platform not only to look in on the lives of vital grandparents but paints, in broad strokes, a mural of coming, changing, as well as challenging cultural and social settings…. In what the astute editors ….call “small nuanced studies” we find telling narratives of generational connections in the face of changing and challenging odds….This book does a great service to the concept of diaspora, as well as to the changing nature of that concept… This book elevates the status of grandparents by positioning them as vital members of a complex and challenging society where their skills, gifts, and sheer presence are most formative…. As is strongly advocated in this book, it is essential that educators, curriculum developers, and teachers appreciate the place of grandparents in their students’ lives.”.